PREVENTIVE EFFORTS FOR PREGNANT WOMEN'S DENTAL HEALTH THROUGH STRUCTURED COUNSELING AND CLINICAL EXAMINATION IN BABADAN VILLAGE - Hayati, Anis Khoirin; Rosyidah, Rafhani Rosyidah; Salma Tsaniyah; Davinaiella R G Prameswari (Journal of Social Comunity Services, 2025)
Objective: This community service program aimed to improve pregnant women’s oral health literacy through a structured educational and clinical intervention in Babadan Village, Ngancar District, Kediri Regency. Poor oral health during pregnancy has been associated with complications such as premature birth and low birth weight, yet awareness and access to dental care remain limited, especially in rural areas. This initiative responded to the high prevalence of untreated dental conditions and the persistence of local myths discouraging pregnant women from seeking dental treatment. Method: The intervention adopted a quantitative pre-experimental design, utilizing pre-test and post-test evaluations to measure knowledge change among participants. Educational sessions were conducted using culturally adapted visual media, combining lectures, discussions, and demonstrations to address the participants’ knowledge gaps. Clinical examinations followed, carried out by certified dentists in accordance with WHO diagnostic standards, to identify the prevalence of dental issues such as caries and gingivitis. Post-test assessments were used to evaluate the effectiveness of the educational approach. Results: Findings demonstrated a significant increase in average knowledge scores—from 55 before the intervention to 85 afterward—highlighting the success of the communication strategies and community-centered approach. Moreover, early indications of behavioral change were observed, such as participants expressing intent to seek routine dental care and adopt proper brushing techniques. This program not only addressed immediate health education needs but also laid a foundation for sustained improvements in maternal oral health practices. Novelty: This intervention model is scalable and adaptable for similar rural contexts, underscoring the critical role of health education in preventive maternal care and community empowerment.